The degree of Availability of the Common Core State Standards for Mathematics on the Data area in developed mathematics book of the basic fourth grade in Syria (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The current research aims to identify the degree of availability of the Common Core State Standards for Mathematics on the area of  Data  in developed mathematics book of the basic fourth grade in Syria.in order to achieve this purpose, the researcher adopted the analytical descriptive approach and used the content analysis method was. The research sample included subjects of  Data contained in developed mathematics book of the basic fourth grade in the Unite one (Graphical Representations) which included three lessons, approved by the Ministry of Education in Syria for the academic year (2024-2023). The results showed that the main Standards (Represent and Interpret data) and it's substances in The area of data of the current standards in the CCSSM standards were 0% which is considered as "Nil and Low" .The researcher proposed that the authors of textbooks  have to be attention about the newest international standards for mathematics ,encourage them to develop the content of The area of data and present it in gradually by the basic education stages according to the CCSSM standards , keep up with the international mathematics textbooks.
Keywords: The common core state standards for mathematics; data; basic fourth gr